2011
DOI: 10.1128/aem.01526-10
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the Soil Metagenome for Studies of Microbial Diversity

Abstract: Soil microbial communities contain the highest level of prokaryotic diversity of any environment, and metagenomic approaches involving the extraction of DNA from soil can improve our access to these communities. Most analyses of soil biodiversity and function assume that the DNA extracted represents the microbial community in the soil, but subsequent interpretations are limited by the DNA recovered from the soil. Unfortunately, extraction methods do not provide a uniform and unbiased subsample of metagenomic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
189
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(210 citation statements)
references
References 45 publications
11
189
0
10
Order By: Relevance
“…Although some level of replication in soil metagenomic studies is now financially feasible, other issues remain (Knight et al, 2012;Lombard et al, 2011). Working with a soil from a single location, Delmont et al (2012a) found that DNA extraction protocols displayed greater variation in metagenomic composition than either soil depth or season of sampling, which was perhaps a surprising result but is consistent with their earlier observation using other molecular methods (Delmont et al, 2011). Because current metagenomic sequencing typically requires a few hundred nanograms of DNA, soils that yield small amounts of DNA, such as permafrost soils, may require additional DNA amplification, a step that may introduce some bias (Mackelprang et al, 2011;Yergeau et al, 2010).…”
Section: Obtaining a Representative Samplesupporting
confidence: 74%
“…Although some level of replication in soil metagenomic studies is now financially feasible, other issues remain (Knight et al, 2012;Lombard et al, 2011). Working with a soil from a single location, Delmont et al (2012a) found that DNA extraction protocols displayed greater variation in metagenomic composition than either soil depth or season of sampling, which was perhaps a surprising result but is consistent with their earlier observation using other molecular methods (Delmont et al, 2011). Because current metagenomic sequencing typically requires a few hundred nanograms of DNA, soils that yield small amounts of DNA, such as permafrost soils, may require additional DNA amplification, a step that may introduce some bias (Mackelprang et al, 2011;Yergeau et al, 2010).…”
Section: Obtaining a Representative Samplesupporting
confidence: 74%
“…Despite recommendations regarding hay preservation and baling conditions, farmers still develop an S. rectivirgula-specific humoral immune response, suggesting intense and continuous exposure. Our results demonstrate the complexity of bioaerosol components in dairy barns which could play a role in occupational respiratory diseases.M icrobial flora from natural sources, such as water, soil, plants, and animals, are well known and studied (14,19,41,43). Yet little information on bioaerosols is available.…”
mentioning
confidence: 99%
“…M icrobial flora from natural sources, such as water, soil, plants, and animals, are well known and studied (14,19,41,43). Yet little information on bioaerosols is available.…”
mentioning
confidence: 99%
“…Os métodos moleculares, independentes de cultivo, passaram a ser amplamente utilizados nos estudos de comunidades microbianas, possibilitando assim a identificação de milhares de microrganismos sem a necessidade da obtenção de culturas e reforçando a noção de que as 13 espécies não cultiváveis correspondem à principal fração da diversidade microbiana de nosso planeta (Handelsman, 2004). Durante anos, acreditou-se que as análises moleculares permitiriam a superação das limitações nos estudos microbiológicos impostos pelas dificuldades no estabelecimento de culturas laboratoriais e diversos trabalhos passaram a ter, e ainda têm, esse enfoque (Rondon et al, 1999; Streit & Schimitz, 2004;Tringe et al, 2005;Sogin et al, 2006;Delmont et al, 2011).No entanto, embora as técnicas de biologia molecular tenham contribuído de forma significante para a ecologia e filogenia microbiana e avanços na área da biotecnologia tenham sido feitos utilizando-se esses métodos, o cultivo dos microrganismos ainda é imprescindível para o entendimento de diversos aspectos da sua biologia e de suas relações intra-e interespecíficas. A importância do estabelecimento de culturas laboratoriais de microrganismos ambientais vem sendo enfatizada cada vez mais, sendo que debates relacionados às dificuldades associadas ao cultivo e propostas de soluções para superá-las têm sido feitos por alguns autores (Zengler et al, 2002;Alain & Querellou, 2009).…”
unclassified